Approach to Fibromyalgia and the Role of Phytotherapy in Treatment - AKÇAKAYA, ADEM; AKÇAKAYA A. (My University, 2024)
Fibromyalgia (FM) is characterized by chronic widespread pain accompanied by fatigue, poor sleep quality, and numerous accompanying conditions. Its prevalence worldwide is around 2.7%, and it is more common in women. Although its epidemiology and pathophysiology cannot be precisely explained, it is known that various factors coexist. Over the years, guidelines containing various criteria have been established for the diagnosis of the disease. The goal of treatment in FM is to improve the patient\"s quality of life and minimize symptoms as much as possible. The success of treatment in FM is limited. Many patients seek alternative treatment methods, including diet and lifestyle changes. Recently, medical nutritional therapies and phytotherapy products have been at the forefront of research in this area. Phytotherapy products can be added alone or in combination with other treatment methods and can enhance the success of treatment. In this article, the epidemiology, pathophysiology, diagnostic methods, pharmacological and non-pharmacological methods used in the treatment of FM syndrome will be discussed, and the most widely used phytotherapeutic products will be addressed.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine